A stochastic variant of Wallenberg syndrome with ipsilateral central facial palsy - K Venugopal; D P Kushal; G Shyamala; M Z Mohammed; Shankar Naik; D P Santosh Kumar (Journal of Mahatma Gandhi Institute of Medical Sciences, 2016)
Lateral medullary syndrome or Wallenberg syndrome is an interesting clinical entity with varied presentations. Its clinical features include ipsilateral Hornerfs syndrome, ataxia, pain, numbness, decreased sensation over face, palate, pharynx, vocal cord palsy, dysphagia, dysarthria and contralateral decreased sensation of pain and temperature over trunk and extremities. However, variability in the presentation of this syndrome is the rule, as illustrated in this case presentation and literature review. Facial nerve involvement can occur in variant of lateral medullary syndrome with pontomedullary sulcus infarct. Its involvement in pure lateral medullary infarct is very unusual. We hereby report a case of a 55-year-old male with classical features of lateral medullary syndrome with ipsilateral central facial palsy. Magnetic resonance imaging brain showed dorsolateral medullary infarct. The facial nerve involvement can be explained by possible damage to ascending the hypothetical looping pathway of supranuclear cortico.facial fibers, which is dispersed in dorsolateral medulla.